Characterizing the protective effects of SHLP2, a mitochondrial-derived peptide, in macular degeneration. Issue 1 (December 2018) - Nashine, Sonali; Cohen, Pinchas; Nesburn, Anthony; Kuppermann, Baruch; Kenney, M.
Abstract Mitochondrial-derived peptides (MDPs) are rapidly emerging therapeutic targets to combat development of neurodegenerative diseases. SHLP2 (small humanin-like peptide 2) is a newly discovered MDP that is coded from theMT-RNR2 (Mitochondrially encoded 16S rRNA) gene in mitochondrial DNA (mtDNA). In the current study, we examined the biological consequences of treatment with exogenously-added SHLP2 in anin vitro human transmitochondrial age-related macular degeneration (AMD) ARPE-19 cell model. In AMD cells, we observed significant down-regulation of the MDP-codingMT-RNR2 gene, and remarkably reduced levels of all five oxidative phosphorylation (OXPHOS) complex I-V protein subunits that are involved in the electron transport chain; these results suggested mitochondrial toxicity and abnormal OXPHOS complex protein subunits' levels in AMD cells. However, treatment of AMD cells with SHLP2: (1) restored the normal levels of OXPHOS complex protein subunits, (2) prevented loss of viable cells and mitochondria, (3) increased the number of mtDNA copies, (4) induced anti-apoptotic effects, and (5) attenuated amyloid-β-induced cellular and mitochondrial toxicity. Cumulatively, our findings established the protective role of SHLP2 in AMD cellsin vitro . In conclusion, this novel study supports the merit of SHLP2 in the treatment of AMD, a primary retinal disease that is a leading cause of blindness among the elderly population in the United States as well as worldwide.